Selection of thin-film-integrable substrates for THz modulator - Tong Liu; Jia Ran; Wen Dong; Qiushuo Sun; Xiao Yu; Long Chen; Guangzu Zhang; Wei Luo; Qiuyun Fu; Shenglin Jiang (Journal of Advanced Dielectrics)
The integrable substrate for THz modulation directly influences both the quality of films and THz absorption. Currently, the available THz substrate candidate library is still not clear. Here, we have carried out a systematic investigation of commonly used commercial substrates, including Si, quartz SiO2, MgO, Al2O3, GdScO3 and TbScO3 in the range of 0.4–1.6[Formula: see text]THz. It is found that low resistance Si, TSO and GSO are certainly not appropriate for THz light modulation due to their relatively higher absorption and dielectric constant, while the rest show better THz transmittance, low refractive index and loss. However, the dielectric constant and refractive index of high resistance Si are generally two times larger than quartz SiO2, Al2O3 and MgO. Compared with Al2O3 and MgO, quartz SiO2 shows at least 50% lower dielectric constant, refractive index and absorption, making it the best candidate. Our research is believed to build the rich substrate candidate library for THz range light modulation.